UNSUR KOMUNIKASI PADA PROSES PEMBELAJARAN DI TAMAN KANAK-KANAK (TK) TUNAS JAYA DESA JELUTUNG KECAMATAN SUNGAILIAT KABUPATEN BANGKA - Hidayati, Yuli Hidayati (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This research discusses the elements of communication in the learning process at Tunas Jaya Sungailiat Kindergarten (TK) in Bangka. The theory used is based on the elements of communication according to Lasswell, which consist of communicator, message, communicant, media, and effect. The research design employed is descriptive with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The research findings indicate that the elements of communication in the learning process at TK Tunas Jaya have been executed effectively. These elements include: Communicator, represented by the teachers at TK Tunas Jaya in the Sungailiat Sub-district, Bangka Regency. Message, conveyed by teachers in both verbal and non-verbal forms. Communicant, involving TK students and their parents. Media, utilizing smartphones supporting the WhatsApp application, enabling communication in groups. Effect, resulting in increased activity among children in the learning process. Based on these findings, it is suggested to improving their communication skills to effectively convey messages to children. Teachers are also encouraged to introduce other innovations in the learning process, ensuring that all early childhood students with diverse characteristics can quickly grasp the learning material.